Electrolyte and battery

By using electrolyte containing fluorine sulfonamide internal salt in lithium-ion batteries, a dense CEI film is formed and the oxidation resistance of the positive electrode material is improved, the problem of poor high-temperature cycling and high-temperature storage performance of lithium-ion batteries at high voltage is solved, and higher battery performance and stability are achieved.

CN119725724AActive Publication Date: 2025-03-28ZHUHAI COSMX BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411922320.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Lithium-ion batteries have poor high-temperature cycling and high-temperature storage performance at high voltages, mainly due to solvent decomposition, gas production and corrosive substance generation, resulting in SEI film damage and electrode material corrosion.

Method used

Using an electrolyte containing fluorine sulfonamide inner salt, a dense CEI film is formed and the oxidation resistance of the positive electrode material is improved by improving the high-temperature cycle performance and high-temperature storage performance of the battery through high electronegativity and high-energy sulfonamide group in the fluorine sulfonamide inner salt.

Benefits of technology

By forming a dense CEI film and improving the oxidation resistance of the positive electrode material, the high-temperature cycling and high-temperature storage performance of lithium-ion batteries at high voltages are significantly improved, the internal resistance of the battery is reduced, and the rate performance and fast charging and discharge capability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208339360000021
    Figure BDA0005208339360000021
  • Figure BDA0005208339360000022
    Figure BDA0005208339360000022
  • Figure BDA0005208339360000041
    Figure BDA0005208339360000041
Patent Text Reader

Abstract

The present invention provides an electrolyte and a battery, the electrolyte comprises a fluorine-containing sulfamide inner salt, the fluorine-containing sulfamide inner salt has a structure represented by a formula 1, and R1-R5 are independently selected from a C1-C12 alkyl group, a halogen atom-containing C1-C12 alkyl group, a halogen atom, and a substituted or unsubstituted aryl group. The electrolyte provided by the invention can improve the high-temperature cycle performance and high-temperature storage performance of the battery under high voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrolyte, in particular to an electrolyte and a battery, belonging to the field of ion batteries. Background Art

[0002] With the development of science and technology and the increase in market demand, the application areas of lithium-ion batteries are expanding day by day, from consumer electronics to electric vehicles, energy storage systems and other fields, and the requirements for battery performance are getting higher and higher. With the update and iteration of technology, the design of electronic products is becoming thinner and lighter, which also puts forward more stringent requirements on the energy density of lithium-ion batteries. Under the condition of a certain volume of lithium batteries, the energy density can be improved by increasing the upper limit voltage and other means.

[0003] However, as the voltage continues to increase (>4.55V), the oxidation of the electrolyte by the release of oxygen by the positive electrode active material continues to intensify, resulting in the decomposition and gas production of the solvent. The decomposition of the lithium salt will also continue to increase, generating more HF and other corrosive substances, destroying the SEI film and corroding the electrode materials. At the same time, the transition metal ions of the positive electrode continue to dissolve and migrate to the surface of the negative electrode, causing certain damage to the SEI film. Under high temperature conditions, the decomposition and gas production of the solvent will be further intensified, and the corrosive substances such as HF will be more corrosive to the SEI film and electrode materials, resulting in the degradation of the high-temperature cycle performance and high-temperature storage performance of the battery under high voltage.

[0004] Therefore, those skilled in the art are in urgent need of developing an electrolyte with high stability to improve the high-temperature cycle performance and high-temperature storage performance of the battery under high voltage. Summary of the invention

[0005] The present invention provides an electrolyte which can improve the high-temperature cycle performance and high-temperature storage performance of a battery under high voltage.

[0006] The present invention provides an electrolyte, comprising a fluorinated sulfonamide inner salt, wherein the fluorinated sulfonamide inner salt has a structure shown in Formula 1:

[0007]

[0008] R1 to R5 are each independently selected from a C1 to C12 alkyl group, a C1 to C12 alkyl group containing a halogen atom, a halogen atom, and a substituted or unsubstituted aryl group.

[0009] The electrolyte as described above, wherein R1 to R5 are each independently selected from C1 to C6 alkyl groups, C1 to C6 alkyl groups containing fluorine atoms, fluorine atoms, substituted or unsubstituted aryl groups, and when the aryl group has a substituent, the substituent is selected from C1 to C6 alkyl groups.

[0010] The electrolyte as described above, wherein the fluorinated sulfonamide inner salt comprises one or more of the compounds represented by the following formulas 1-1 to 1-5:

[0011]

[0012] In the electrolyte as described above, the mass percentage ml of the fluorinated sulfonamide inner salt in the electrolyte is 0.1% to 20%, preferably, m1 is 0.5% to 10%.

[0013] The electrolyte as described above, wherein the electrolyte comprises a carboxylate solvent;

[0014] Preferably, the carboxylate solvent comprises at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate and ethyl n-butyrate;

[0015] Preferably, the mass percentage m2 of the carboxylate solvent in the electrolyte is 5% to 50%.

[0016] The electrolyte as described above, wherein the electrolyte comprises a lithium salt, and the lithium salt comprises a boron-containing lithium salt;

[0017] Preferably, the boron-containing lithium salt comprises lithium difluorooxalate borate;

[0018] Preferably, the mass percentage m3 of the boron-containing lithium salt in the electrolyte is 0.1% to 1%.

[0019] The electrolyte as described above, wherein the electrolyte comprises vinyl sulfate;

[0020] Preferably, the mass percentage m4 of the vinyl sulfate in the electrolyte is 0.1% to 1%.

[0021] The present invention provides a battery, which comprises a positive electrode sheet, a negative electrode sheet and the electrolyte as described above.

[0022] The battery as described above, wherein the negative electrode sheet comprises a negative electrode active material, the negative electrode active material comprises a carbon-based material and a silicon-based material, and / or the porosity of the negative electrode sheet is 50% to 70%;

[0023] Preferably, the mass percentage m5 of silicon element in the negative electrode active material is 2% to 30%;

[0024] Preferably, the D50 of the silicon-based material is 5 μm to 15 μm.

[0025] The battery as described above, wherein the positive electrode sheet comprises a lithium cobalt oxide material;

[0026] Preferably, the mass percentage content m6 of the cobalt element in the lithium cobalt oxide material is 54.8% to 63.1%.

[0027] The electrolyte of the present invention comprises a fluorinated sulfonamide inner salt. When the electrolyte comprising the fluorinated sulfonamide inner salt is applied to a battery, on the one hand, the high electronegativity of the fluorine atoms in the fluorinated sulfonamide inner salt enables the fluorinated sulfonamide groups to have strong adsorption on the positive electrode surface, and can preferentially interact with the surface of the positive electrode material to form a dense CEI film, and the dense CEI film can improve the high-temperature cycle performance and high-temperature storage performance of the battery under high voltage; on the other hand, the high energy level of the fluorinated sulfonamide groups in the fluorinated sulfonamide inner salt enables the positive electrode material to have strong oxidation resistance, thereby improving the high-temperature cycle performance and high-temperature storage performance of the battery under high voltage. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0029] The present invention provides an electrolyte, comprising a fluorinated sulfonamide inner salt, wherein the fluorinated sulfonamide inner salt has a structure shown in Formula 1:

[0030]

[0031] R1 to R5 are each independently selected from a C1 to C12 alkyl group, a C1 to C12 alkyl group containing a halogen atom, a halogen atom, and a substituted or unsubstituted aryl group.

[0032] The C1-C12 alkyl group in the embodiments of the present invention refers to a chain alkyl group with 1 to 12 carbon atoms or a cycloalkyl group with 3 to 12 carbon atoms.

[0033] The C1-C12 alkyl group containing halogen atoms in the embodiments of the present invention refers to a chain alkyl group with 1 to 12 carbon atoms or a cycloalkyl group with 3 to 12 carbon atoms substituted by a halogen atom.

[0034] The halogen atom in the embodiment of the present invention refers to a fluorine atom, a bromine atom, an iodine atom, and the like.

[0035] The substituted or unsubstituted aryl group in the embodiments of the present invention refers to an aryl group having a substituent or an aryl group having no substituent. When a substituent is specified as a group having a specific carbon number, all geometric isomers having the carbon number are included.

[0036] Illustratively, R1 to R5 are each independently selected from -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CF3, -CCl3, -CBr3, -CH2CF3, -CH2CH2CF3, -F, -Cl, -I, -C6H5, -C6F5, -C6H4-CH3, -C6H4-F, etc.

[0037] The electrolyte of the embodiment of the present invention includes a fluorinated sulfonamide inner salt, and when the fluorinated sulfonamide inner salt has the above structure, it can improve the high temperature cycle performance and high temperature storage performance of the battery at high voltage. The inventor analyzed this principle and believed that the reason may be that, on the one hand, the high electronegativity of the fluorine atoms in the fluorinated sulfonamide inner salt makes the fluorinated sulfonamide group have strong adsorption on the positive electrode surface, and can preferentially interact with the surface of the positive electrode material to form a dense CEI film, which can effectively cover the positive electrode transition metal site, protect the positive electrode active material, and avoid the damage of the SEI film caused by the dissolution of the positive electrode transition metal; on the other hand, the high energy level of the fluorinated sulfonamide group in the fluorinated sulfonamide inner salt makes the positive electrode material have strong antioxidant properties, thereby improving the high temperature cycle performance and high temperature storage performance of the battery at high voltage; in addition, the fluorinated sulfonamide inner salt can form a stable ion pair in the electrolyte and promote the rapid transmission of lithium ions, which helps to reduce the internal resistance of the battery and improve the rate performance and rapid charge and discharge capability of the battery.

[0038] In a specific embodiment, R1~R5 are each independently selected from C1~C6 alkyl, C1~C6 alkyl containing halogen atoms, halogen atoms, substituted or unsubstituted aryl groups. When the aryl group has a substituent, the substituent is selected from C1~C6 alkyl. Exemplarily, R1~R5 are each independently selected from -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CF3, -CH2CF3, -CH2CH2CF3, -CH(CF3)2, -C6H4-CH3, -C6H4CH2CH3, -C6H4CH2CH2CH3, -C6H3(CH3)2, -C6H3(CH2CH3)2, -C6H2(CH3)3, etc.

[0039] In a specific embodiment, the fluorinated sulfonamide inner salt includes one or more of the compounds shown in the following formulas 1-1 to 1-5:

[0040]

[0041] When the fluorinated sulfonamide inner salt is selected from the above compounds, the fluorinated sulfonamide inner salt makes the positive electrode material more resistant to oxidation, thereby further improving the high-temperature cycle performance and high-temperature storage performance of the battery at high voltage.

[0042] In a specific embodiment, the mass percentage m1 of the fluorinated sulfonamide inner salt in the electrolyte is 0.1% to 20%, for example, 0.1%, 0.5%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, etc. Preferably, m1 is 0.5% to 10%. When the mass percentage of the fluorinated sulfonamide inner salt is within the above range, a sufficient amount of the fluorinated sulfonamide inner salt can form a CEI film of sufficient thickness on the surface of the positive electrode, so that the stability of the CEI film is higher, thereby better protecting the positive electrode active material and avoiding damage to the SEI film caused by the dissolution of the positive electrode transition metal; on the other hand, a sufficient amount of the fluorinated sulfonamide inner salt makes the positive electrode material have stronger oxidation resistance, thereby further improving the high temperature cycle performance and high temperature storage performance of the battery under high voltage.

[0043] In a specific embodiment, the electrolyte includes a carboxylate solvent; preferably, the carboxylate solvent includes at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate and ethyl butyrate; preferably, the mass percentage m2 of the carboxylate solvent in the electrolyte is 5% to 50%, for example, 5%, 10%, 20%, 30%, 40% or 50%. When a carboxylate solvent is selected and the mass percentage of the solvent is within the above range, the carboxylate solvent can completely dissolve the fluorinated sulfonamide inner salt, which is beneficial to the improvement of the high temperature cycle performance, high temperature storage performance and low temperature discharge performance of the battery.

[0044] In a specific embodiment, the electrolyte includes a lithium salt, and the lithium salt includes a boron-containing lithium salt; preferably, the boron-containing lithium salt includes lithium difluorooxalate borate (LiODFB). When the boron-containing lithium salt is selected as LiODFB, the lithium difluorooxalate borate can form a dense protective film on the surface of the positive electrode, and this protective film can better inhibit the oxidation reaction of the lithium difluorooxalate borate on the positive electrode at high potential. This inhibitory effect increases the stability of the lithium-ion battery using lithium difluorooxalate borate as the electrolyte.

[0045] Preferably, the mass percentage m3 of the boron-containing lithium salt in the electrolyte is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc. When the mass percentage of the boron-containing lithium salt is within the above range, the boron-containing lithium salt can form a more stable complex layer at the positive electrode, thereby better protecting the positive electrode active material, improving the high temperature cycle performance and high temperature storage performance of the battery, and avoiding the side reaction of the boron-containing lithium salt with other components in the battery due to excessive addition of the boron-containing lithium salt, thereby avoiding the degradation of the electrochemical performance.

[0046] In a specific embodiment, the lithium salt further comprises one or more of lithium hexafluorophosphate, lithium difluorophosphate and lithium tetrafluoroborate; preferably, the lithium salt accounts for 5% to 25% by mass of the electrolyte, for example, 5%, 10%, 15%, 20% or 25%, and preferably the lithium salt comprises lithium hexafluorophosphate (LiPF6). When the mass percentage of the lithium salt is within the above range, the lithium salt can be completely dissolved in the organic solvent to form an electrolyte with high stability, so that lithium ions can be quickly dissociated and transported in the electrolyte, thereby improving the conductivity of the electrolyte and thus improving the electrochemical performance of the battery.

[0047] In a specific embodiment, the electrolyte includes vinyl sulfate (DTD). The addition of fluorinated sulfonamide inner salts in the electrolyte can form a stable protective film on the surface of the positive electrode, protect the positive electrode active material, and improve the high-temperature cycle performance and high-temperature storage performance of the battery under high voltage. However, the conductivity of the protective film is not high enough, which causes the impedance of the battery to increase, resulting in the degradation of the low-temperature discharge performance of the battery. In order to improve the low-temperature discharge performance of the battery, the embodiment of the present invention adds DTD to the electrolyte. DTD can change the coordination environment of the positive electrode metal ions and the fluorinated sulfonamide inner salts, reduce the activity of the metal ions, reduce the reaction of the metal ions with other components in the electrolyte, avoid the electrolyte solvent from oxidizing and decomposing at an increased rate, and can reduce impedance, thereby reducing the impedance of the positive electrode and improving the low-temperature discharge performance of the battery. Moreover, DTD can participate in the construction of the SEI film, effectively improve the flexibility and stability of the SEI film, and avoid the volume change of the negative electrode material during the charge and discharge process causing the SEI film to rupture, thereby improving the cycle performance of the battery.

[0048] Preferably, the mass percentage m4 of DTD in the electrolyte is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc. When the mass percentage of DTD is within the above range, DTD can better reduce the impedance of the positive electrode and make the flexibility and stability of the SEI film better, and at the same time, it can avoid excessive DTD causing side reactions between DTD and other components in the electrolyte, so that the battery exhibits higher low-temperature discharge performance and cycle performance.

[0049] The present invention provides a battery, which comprises a positive electrode sheet, a negative electrode sheet and the above electrolyte, and exhibits excellent high-temperature cycle performance and high-temperature storage performance at high voltage.

[0050] In a specific embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder, wherein the negative electrode current collector is generally a copper foil. The negative electrode active material includes a carbon-based material and a silicon-based material. When the negative electrode active material includes a carbon-based material and a silicon-based material, the silicon-based material can improve the energy density of the battery, and the carbon-based material can suppress the expansion problem caused by the silicon-based material, improve the diffusion rate and transmission rate of lithium ions in silicon particles, thereby ensuring the cycle performance of the battery.

[0051] Preferably, the mass percentage m5 of silicon in the negative electrode active material is 2% to 30%, for example, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, etc. When the mass percentage of silicon in the negative electrode active material is within the above range, the conductivity of the negative electrode sheet is high, and the expansion rate of the negative electrode active material layer is low during the battery charging and discharging process, avoiding the problem of pulverization and shedding of the negative electrode active material layer, thereby improving the cycle performance and safety performance of the battery.

[0052] Specifically, the mass percentage of silicon in the negative electrode active material can be obtained by inductively coupled plasma spectrometry (ICP) testing.

[0053] Preferably, the D50 of the silicon-based material is 5 μm to 15 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm, etc. When the D50 of the silicon-based material is within the above range, the silicon particles can have a certain buffer space when the volume changes, reducing the risk of material breakage and improving the cycle stability of the battery.

[0054] Specifically, the D50 test method of the silicon-based material includes the following steps:

[0055] The battery was disassembled, the negative electrode sheet was taken out, the silicon-carbon negative electrode powder on the current collector was scraped off, and the scraped powder sample was ground and sieved so that the average particle size of the particles was controlled within a certain range (such as 320 mesh, about 40 μm) and the particles were evenly distributed. Then, the sample was scanned using an X-ray diffractometer to obtain the D50 of the silicon-based material.

[0056] In a specific embodiment, the porosity of the negative electrode sheet is 50% to 70%, such as 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68% or 70%, etc. The increase in porosity means that the proportion of unoccupied pore space in the negative electrode material increases, which helps to increase the specific surface area of the material. The increase in specific surface area provides more active sites for the insertion and extraction of lithium ions, thereby increasing the energy storage capacity of the battery. At the same time, it provides a certain buffer space to reduce the stress and strain generated by the volume change of the negative electrode material, thereby improving the cycle stability of the battery.

[0057] Specifically, the test method for the porosity of the negative electrode sheet includes the following steps: disassemble the battery, take out the electrode sheet and dry it, and then use CT technology on the negative electrode sheet to obtain the three-dimensional structure and morphological information inside the negative electrode sheet, including the size, shape and distribution of pores, etc. Then, through three-dimensional reconstruction and data analysis, parameters such as porosity can be accurately calculated.

[0058] In a specific embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer provided on the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. Among them, the positive electrode current collector is generally a copper foil. The positive electrode active material includes lithium cobaltate material. The lithium cobaltate material selected in the embodiments of the present invention can effectively improve the specific capacity of the battery.

[0059] Specifically, the mass percentage content of cobalt element in the lithium cobaltate material is obtained by testing with inductively coupled plasma spectroscopy (ICP).

[0060] Preferably, the mass percentage content m6 of cobalt element in the lithium cobaltate material is 54.8% to 63.1%, such as 54.8%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62% or 63.1%, etc. When the mass percentage content of cobalt element in the lithium cobaltate is within the above range, it can improve the specific capacity of the battery and avoid problems such as capacity decline and poor cycle performance caused by the system expansion of the positive electrode material, thereby ensuring that the battery reaches higher electrochemical performance under high-capacity conditions.

[0061] In a specific embodiment, the carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon and soft carbon; and / or, the silicon-based material is selected from at least one of nano-silicon (Si), silicon-based negative electrode material (SiOx(0 < x < 2)) and silicon-carbon negative electrode material.

[0062] In a specific embodiment, the electrolyte further includes conventional additives, which include at least one of vinylene carbonate, vinyl carbonate, fluoroethylene carbonate, vinyl sulfate, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sunflower dinitrile, 1,3,6-hexanetrinitrile, glycerol trinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3-propanesultone and propenyl-1,3-sultone.

[0063] In a specific embodiment, the negative electrode active material layer further includes a conductive agent and a binder; the positive electrode active material layer further includes a conductive agent and a binder.

[0064] In a specific embodiment, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.

[0065] In a specific embodiment, the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0066] In a specific embodiment, the battery further includes a separator, which is a separator known in the art that can be used in batteries and is stable to the electrolyte used, and can be specifically configured as required.

[0067] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0068] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.

[0069] Example 1

[0070] The battery provided in this embodiment is prepared by the following steps:

[0071] 1. Preparation of electrolyte: In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC) / propylene carbonate (PC) / diethyl carbonate (DEC) / propyl propionate (PP) were mixed in a mass ratio of 8 / 8 / 15 / 50, and then 13wt% of fully dried lithium hexafluorophosphate (LiPF6) based on the total mass of the electrolyte was quickly added thereto, and after dissolution, 4wt% of 1,3-propane sultone (PS) and 8wt% of fluoroethylene carbonate based on the total mass of the electrolyte were added, and fluorinated sulfonamide inner salt, LiODFB and DTD were added according to the additives shown in Table 1, and the electrolyte was prepared after mixing;

[0072] 2. Preparation of negative electrode sheet: artificial graphite, silicon-carbon material (D50 is 15 μm), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) of negative electrode active materials are mixed in a mass ratio of 94.5:2.5:1.5:1:0.5, deionized water is added, and negative electrode active slurry is obtained under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on both surfaces of the copper foil; the coated copper foil is dried at room temperature, then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet;

[0073] 3. Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide (LiCoO2, D50 is 15.54μm, D90 is 28.89μm), polyvinylidene fluoride (PVDF), SP (superP) and carbon nanotubes (CNT) in a mass ratio of 96:2:1.5:0.5, add N-methylpyrrolidone (NMP), and stir under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; evenly coat the positive electrode active slurry on both surfaces of the aluminum foil; dry the coated aluminum foil, and then roll and cut it to obtain the required positive electrode sheet;

[0074] 4. Preparation of the battery: stack the positive electrode sheet, the negative electrode sheet and the separator in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wind them to obtain a battery cell; place the battery cell in an outer packaging aluminum foil, inject the electrolyte into the outer packaging, and obtain the battery through vacuum packaging, standing, forming, shaping, sorting and other processes. The charge and discharge range of the battery of the present invention is 3.0-4.58V.

[0075] Examples 2 to 52, Comparative Example 1, Comparative Example 2: The differences from Example 1 are shown in Table 1. Except for the differences shown in Table 1, the other conditions are the same. Among them, the structure of the pyridine propane sulfonic acid inner salt in Comparative Example 1 is

[0076] The mass percentage of cobalt element in lithium cobalt oxide material was tested by ICP, as shown in Table 1.

[0077] The negative electrode sheet was tested by a true density meter to obtain the porosity of the negative electrode sheet, as shown in Table 1.

[0078] True density meter porosity test method:

[0079] Place the sample into the true density meter and use a weighing device to measure the mass of the sample.

[0080] The actual volume of the sample is determined by gas expansion displacement (eg using helium).

[0081] Calculate the true density, which is the mass divided by the true volume.

[0082] Measuring the apparent density:

[0083] The sample is placed in a container and the mass of the entire container is measured.

[0084] The apparent density is calculated by measuring the volume of the container and the mass of the sample.

[0085] Calculate the porosity: According to the porosity formula: Porosity = (apparent density - true density) / apparent density × 100%, substitute the true density and apparent density into the formula to calculate the porosity.

[0086] Table 1

[0087]

[0088]

[0089]

[0090] Test example

[0091] The lithium ion batteries obtained in the examples and comparative examples were subjected to high temperature cycle performance test, high temperature storage performance test, low temperature discharge performance test and rate test, respectively. The test results are shown in Table 2.

[0092] 1) 45℃ high temperature cycle performance test

[0093] The batteries prepared in the examples and comparative examples were charged and discharged for 600 cycles at 45°C at a rate of 1C within the charge and discharge cut-off voltage range. The discharge capacity in the first week of the test was calculated as x1 mAh, and the discharge capacity in the Nth week was calculated as y1 mAh. The capacity in the Nth week was divided by the capacity in the first week to obtain the cycle capacity retention rate R1=y1 / x1 in the Nth week. See Table 2 for details.

[0094] 2) 25℃ Cyclic Performance Test

[0095] The batteries prepared in the examples and comparative examples were charged and discharged for 600 cycles at 25°C at a rate of 1C within the charge and discharge cut-off voltage range. The discharge capacity in the first week of the test was calculated as x1 mAh, and the discharge capacity in the Nth week was calculated as y1 mAh. The capacity in the Nth week was divided by the capacity in the first week to obtain the cycle capacity retention rate R1=y1 / x1 in the Nth week. See Table 2 for details.

[0096] 3) Low temperature discharge performance test

[0097] The voltage, internal resistance and thickness of lithium-ion batteries were tested at 0°C and left to stand for 10 minutes; discharged at 1C to a lower voltage of 3.0V and left to stand for 10 minutes; fully charged at 1C in a constant temperature room, with a cut-off current of 0.025C and left to stand for 10 minutes; discharged at a rate of 3C to a cut-off voltage of 3.0V in a constant temperature box environment and left to stand for 10 minutes; the discharge capacity Q1 and the initial discharge capacity Q0 were recorded, calculated by Q1 / Q0×100%, and the discharge capacity retention rate was recorded. See Table 2 for details.

[0098] 4) Ratio test

[0099] The voltage, internal resistance and thickness of the lithium-ion battery were tested at 25°C and left to stand for 10 minutes; the battery was discharged at 1C to a lower voltage of 3.0V and left to stand for 10 minutes; the battery was fully charged at 1C in a constant temperature room, with a cut-off current of 0.025C and left to stand for 10 minutes; the battery was discharged at a rate of 3C to a cut-off voltage of 3.0V in a constant temperature box and left to stand for 10 minutes; the discharge capacity Q2 and the initial discharge capacity Q0 were recorded and calculated by Q2 / Q0×100%, and the discharge capacity retention rate was recorded. See Table 2 for details.

[0100] Table 2

[0101]

[0102]

[0103]

[0104] It can be seen from Table 2 that according to Example 1, Comparative Example 1 and Comparative Example 2, the electrolyte can include fluorinated sulfonamide inner salt, which can improve the high-temperature cycle performance and high-temperature storage performance of the battery at high voltage.

[0105] According to the comparison of Examples 1-5, when the usage of the fluorinated sulfonamide inner salt is in the range of 0.5% to 20%, the high temperature cycle performance and high temperature storage performance of the battery under high voltage can be improved.

[0106] According to the comparison of Examples 1 and 6-9, it can be seen that when the mass percentage m4 of DTD in the electrolyte is in the range of 0.1% to 1%, DTD can better reduce the impedance of the positive electrode and make the flexibility and stability of the SEI film better. At the same time, it can avoid excessive DTD causing side reactions between DTD and other components in the electrolyte, thereby making the battery exhibit higher low-temperature discharge performance and cycle performance.

[0107] According to the comparison of Examples 1 and 10-13, when the mass percentage m2 of the carboxylate solvent in the electrolyte is in the range of 5% to 50%, the carboxylate solvent can completely dissolve the fluorinated sulfonamide inner salt, which is beneficial to the improvement of the high temperature cycle performance, high temperature storage performance and low temperature discharge performance of the battery.

[0108] According to the comparison of Examples 1 and 18-21, when the mass percentage m3 of the boron-containing lithium salt in the electrolyte is in the range of 0.1% to 1%, the boron-containing lithium salt can form a more stable complex layer at the positive electrode, thereby better protecting the positive electrode active material and improving the high-temperature cycle performance and high-temperature storage performance of the battery.

[0109] According to the comparison of Examples 1 and 22-26, it can be seen that when the mass percentage m5 of the silicon element in the negative electrode active material is in the range of 2% to 30%, the conductivity of the negative electrode sheet is high, and the expansion rate of the negative electrode active material layer is low during the battery charging and discharging process, avoiding the problem of pulverization and falling off of the negative electrode active material layer, thereby improving the cycle performance and safety performance of the battery.

[0110] According to the comparison of Examples 1 and 27-30, when the D50 of the silicon-based material is in the range of 5 μm to 15 μm, the silicon particles can have a certain buffer space when the volume changes, thereby reducing the risk of material breakage and improving the cycle stability of the battery.

[0111] According to the comparison of Examples 1 and 31-34, it can be seen that when the porosity of the negative electrode sheet is in the range of 50% to 70%, the energy storage capacity and cycle stability of the battery can be improved.

[0112] According to the comparison of Examples 1 and 35-38, when the mass percentage content m6 of the cobalt element in the lithium cobalt oxide material is in the range of 54.8% to 63.1%, the specific capacity of the battery can be improved, and the problems of capacity decrease and cycle performance deterioration caused by the system expansion of the positive electrode material can be avoided, thereby ensuring that the battery achieves higher electrochemical performance under high capacity conditions.

[0113] According to Examples 1 and 39-42, when the fluorinated sulfonamide inner salt is selected as the above-mentioned compound, the fluorinated sulfonamide inner salt makes the positive electrode material more resistant to oxidation, thereby further improving the high-temperature cycle performance and high-temperature storage performance of the battery at high voltage.

[0114] According to the comparison between Examples 1 and 43-44, it can be seen that when the lithium salt includes a boron-containing lithium salt, it is beneficial to improve the stability of the battery.

[0115] According to the comparison of Examples 1, 43 and 45, it can be seen that when DTD is included in the electrolyte, the high temperature cycle performance of the battery can be improved.

[0116] According to Examples 1 and 46-53, the above-mentioned carboxylic acid ester solvents can completely dissolve the fluorinated sulfonamide inner salt, which is beneficial to improving the high-temperature cycle performance, high-temperature storage performance and low-temperature discharge performance of the battery.

[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrolyte, characterized in that: It includes a fluorinated sulfonamide inner salt, wherein the fluorinated sulfonamide inner salt has a structure shown in Formula 1: R1 to R5 are each independently selected from a C1 to C12 alkyl group, a C1 to C12 alkyl group containing a halogen atom, a halogen atom, and a substituted or unsubstituted aryl group.

2. The electrolyte according to claim 1, characterized in that R1 to R5 are each independently selected from a C1 to C6 alkyl group, a C1 to C6 alkyl group containing a fluorine atom, a fluorine atom, and a substituted or unsubstituted aryl group. When the aryl group has a substituent, the substituent is selected from a C1 to C6 alkyl group.

3. The electrolyte according to claim 2, characterized in that The fluorinated sulfonamide inner salt includes one or more compounds represented by the following formulas 1-1 to 1-5:

4. The electrolyte according to any one of claims 1 to 3, characterized in that The mass percentage m1 of the fluorinated sulfonamide inner salt in the electrolyte is 0.1% to 20%, preferably, m1 is 0.5% to 10%.

5. The electrolyte according to any one of claims 1 to 3, characterized in that The electrolyte includes a carboxylate solvent; Preferably, the carboxylate solvent comprises at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate and ethyl n-butyrate; Preferably, the mass percentage m2 of the carboxylate solvent in the electrolyte is 5% to 50%.

6. The electrolyte according to any one of claims 1 to 3, characterized in that: The electrolyte includes a lithium salt, and the lithium salt includes a boron-containing lithium salt; Preferably, the boron-containing lithium salt comprises lithium difluorooxalate borate; Preferably, the mass percentage m3 of the boron-containing lithium salt in the electrolyte is 0.1% to 1%.

7. The electrolyte according to any one of claims 1 to 3, characterized in that: The electrolyte includes vinyl sulfate; Preferably, the mass percentage m4 of the vinyl sulfate in the electrolyte is 0.1% to 1%.

8. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and the electrolyte according to any one of claims 1 to 7.

9. The battery according to claim 8, characterized in that The negative electrode sheet comprises a negative electrode active material, the negative electrode active material comprises a carbon-based material and a silicon-based material, and / or the porosity of the negative electrode sheet is 50% to 70%; Preferably, the mass percentage m5 of silicon element in the negative electrode active material is 2% to 30%; Preferably, the D50 of the silicon-based material is 5 μm to 15 μm.

10. The battery according to claim 8, characterized in that The positive electrode sheet comprises lithium cobalt oxide material; Preferably, the mass percentage content m6 of the cobalt element in the lithium cobalt oxide material is 54.8% to 63.1%.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution, nonaqueous electrolyte solution battery, and compound

    CN116918123A

  • Inner salt type additive containing N and S elements, lithium ion battery electrolyte and application

    CN117080551A

  • Electrolytes for target ion transport

    US20230216086A1

  • Electrolyte additive, electrolyte and lithium-ion secondary battery containing same, and use thereof

    US20240186576A1